Reduction of Nonspecificity Motifs in Synthetic Antibody Libraries. Issue 1 (5th January 2018) - Kelly, Ryan L.; Le, Doris; Zhao, Jessie; Wittrup, K. Dane
Abstract: Successful antibody development requires both functional binding and desirable biophysical characteristics. In the current study, we analyze the causes of one hurdle to clinical development, off-target reactivity, or nonspecificity. We used a high-throughput nonspecificity assay to isolate panels of nonspecific antibodies from two synthetic single-chain variable fragment libraries expressed on the surface of yeast, identifying both individual amino acids and motifs within the complementarity-determining regions which contribute to the phenotype. We find enrichment of glycine, valine, and arginine as both individual amino acids and as a part of motifs, and additionally enrichment of motifs containing tryptophan. Insertion of any of these motifs into the complementarity-determining region H3 of a "clean" antibody increased its nonspecificity, with greatest increases in antibodies containing Trp or Val motifs. We next applied these rules to the creation of a synthetic diversity library based on natural frameworks with significantly decreased incorporation of such motifs and demonstrated its ability to isolate binders to a wide panel of antigens. This work both provides a greater understanding of the drivers of nonspecificity and provides design rules to increase efficiency in the isolation of antibodies with drug-like properties. Graphical abstract: Highlights: Screened two libraries for nonspecific antibodies using a high-throughput yeast display assay Identified motifs containing Trp, Val, Gly, and Arg as drivers of nonspecificity Created a new, Trp-free synthetic library based on natural frameworks that minimized these motifs. Isolated high-affinity binders to a wide panel of antigens.